2014
DOI: 10.1002/bip.22369
|View full text |Cite
|
Sign up to set email alerts
|

Development of advanced antimicrobial and sterilized plasma polypropylene grafted muga (antheraea assama) silk as suture biomaterial

Abstract: Surface modification of silk fibroin (SF) materials using environmentally friendly and non-hazardous process to tailor them for specific application as biomaterials has drawn a great deal of interest in the field of biomedical research. To further explore this area of research, in this report, polypropylene (PP) grafted muga (Antheraea assama) SF (PP-AASF) suture is developed using plasma treatment and plasma graft polymerization process. For this purpose, AASF is first sterilized in argon (Ar) plasma treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Bioceramics have also been used in combination with different biomacromolecules, such as collagen or chitosan, to prepare composite scaffolds to be used as bone implants [ 137 , 138 , 139 , 140 ]. Amongst them, silk fibroin (SF) appears as an interesting material for BTE due to its excellent mechanical and functional properties, low immunogenicity and good biocompatibility [ 137 , 141 ]. Thus, SF has been employed in combination with HA to render SF/HA composite scaffolds with excellent biocompatibility, osteoconductivity, and osteoinductivity [ 142 , 143 ].…”
Section: The Effect Of Substrate Topographymentioning
confidence: 99%
“…Bioceramics have also been used in combination with different biomacromolecules, such as collagen or chitosan, to prepare composite scaffolds to be used as bone implants [ 137 , 138 , 139 , 140 ]. Amongst them, silk fibroin (SF) appears as an interesting material for BTE due to its excellent mechanical and functional properties, low immunogenicity and good biocompatibility [ 137 , 141 ]. Thus, SF has been employed in combination with HA to render SF/HA composite scaffolds with excellent biocompatibility, osteoconductivity, and osteoinductivity [ 142 , 143 ].…”
Section: The Effect Of Substrate Topographymentioning
confidence: 99%
“…Silk broins are classied into two main types namely mulberry (Bombyx mori) and non-mulberry varieties including muga (Antheraea assama), eri (Philosamia ricini), tasar (Antheraea mylitta). 9 Bombyx mori silk broin (BMSF) has been characterised and commercially available biomaterial worldwide for centuries. 10 Among the non-mulberry silk P. ricini and A. assama has been widely studied in the eld of biomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…As shown later in Figure , we observed that the position of peaks present in the diffraction curves of the TFF and CMTFF samples remained unchanged. Gogoi et al . previously reported that the diffraction curves at a 2θ of 20.2 ° were characteristic of the highly ordered antiparallel β‐sheet crystalline structure of the poly(glycine–alanine) chain.…”
Section: Resultsmentioning
confidence: 92%